Genetic relationships among Mycobacterium leprae, Mycobacterium tuberculosis, and candidate leprosy vaccine strains determined by DNA hybridization: identification of an M. leprae-specific repetitive sequence. - Grosskinsky, C M (1989)
Comparative DNA hybridization studies of genomic DNA indicated that, while different isolates of armadillo-derived Mycobacterium leprae have a high degree of homology, binding of M. leprae genomic DNA to DNA of other species of mycobacteria or to corynebacteria was low, establishing that M. leprae is only remotely genetically related to any of the species examined. Several candidate leprosy vaccine mycobacterial strains were similarly found to have little genetic similarity to M. leprae. In contrast, the DNAs of the slow-growing mycobacteria M. tuberculosis, M. africanum, M. bovis, and M. microti were found to be very closely related. In the course of these studies, an M. leprae-specific repetitive sequence, greater than 15-fold per genome equivalent, was identified that might be useful for diagnostic and epidemiological studies.